Development and initial validation of the Career Self-Management scale for Chinese coaches - Zhang, Chonghui; Liu, Jing-Dong (Frontiers in Psychology, 2023)
The purpose of the study was to develop and initially validate a context-specific scale assessing Career Self-Management for Chinese coaches (Career Self-Management Scale-CC; CSMS-CC).Firstly, an initial 18-item CSMS-CC items were developed based on literatures review, qualitative content analysis of in-depth interview with coaches, and feedbacks from experts. Secondly, the factor structure and item performance of the CSMS-CC were examined using exploratory factor analysis (EFA) in sample 1 (n=229, 24.01% females). Results of EFA revealed that eight items were problematic and removed. The second round of EFA revealed that three components were retained and labelled as Networking Behavior (4 items), Training Exploration (3 items), and Guanxi Development (3 items). Thirdly, factor structure of the 10-item CSMS-CC was further examined using confirmatory factor analysis (CFA) in sample 2 (n=295, 32.54% females). Results suggested that the 10-item three-correlated-factors model of CSMS-CC demonstrated acceptable model fit to the data, χ2 = 135.01, df=32, p< 0.01, CFI=.91, TLI=.90, SRMR = 0.05, RMSEA = .092 (90% CI = .076-.108). Composite reliability (ranging from 0.84 to 0.88) and Cronbach's alpha coefficients (ranging from 0.78 to 0.81) of three subscales were found satisfactory. Nomological validity was examined using Pearson correlation and structural equation modeling (SEM) by investigating the correlations between CSMS-CC subscales with career success. It was found that the total score and subscale scores of the CSMS-CC were significantly associated with internal marketability and external marketability, which provided support for the nomological validity. Finally, measurement invariance and latent mean difference of the CSMS-CC was examined across gender, professional Career Self-Management of Chinese Coaches 2 This is a provisional file, not the final typeset article title and coaching class using multiple-group CFA (MGCFA). It was found the CSMS-CC measurement model was strict invariant across gender, professional title and coaching class.Significant differences on all three subscales across professional title and on guanxi development across coaching class were revealed. Collectively, results of this study provided initial support for the psychometric properties of the 10-item CSMS-CC, which suggested that the CSMS-CC could be used for measuring the career self-management of Chinese coaches.